Development of an innovative apparatus using UV‐C for controlling the number of microorganisms in raw milk after milking. (12th September 2019) - Makarapong, David; Tantayanon, Supawan; Gowanit, Chupun; Inchaisri, Chaidate
Abstract : This study was conducted to investigate the effect of UV‐C irradiation on the reduction of microorganisms in raw milk. The experiments were carried out by varying the flow rates of 2, 4 and 7 L/min with 39W and 48W UV‐C. The number of microorganisms was reduced by 4.70 (39W) and 4.60 log10 CFU/mL (48W) at 120 min. With the residence time of 4.95 s and the UV‐C doses of 98 and 109.9 mJ/cm 2 at 253.74 nm, the reduction of microorganism was clearly observed with no significant influence of different UV‐C power settings on the oxidation of milk fat.